A study on the behavior of Filipino customers in the space utilization of dining furniture in fast food restaurants - Chua, Jenna S.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
The purpose of this qualitative study is to explore the behavior of Filipinos in the space utilization of furniture in fast food restaurants. This includes determining the existing types of furniture and compositions, as well as the various customer groups in making a selection among the seating options provided for them in three fast food restaurants.The qualitative research method was used in this study by using an observation guide when inspecting the dining area of the three restaurants, and when recording the attitudes of their customers during the utilization of the space. The study also utilized a focus group discussion among six respondents to discuss the behavior of Filipinos in fast food restaurant dining areas. The findings were cross referenced and analyzed using The Onion Theory of Comfort by Witold Rybczynski, The Theory of Proxemics by Edward Hall, and concepts related to Filipino behaviors and attitudes.The results showed that movable furniture, as opposed to fixed ones, are more efficient in fast food restaurants in the Philippines. Aspects such as the visual perception of comfort, safety and security, flexibility, and space capacity are the main considerations of customers in selecting their seating spaces in the fast food restaurants. Culturally, Filipinos have their own comfort levels in dealing with issues related to proximity. The attitudes pakikipagkapwa and pakikisama among others are still prevalent among Filipinos. The concept of Ibang Tao and Hindi Ibang Tao by Virgilio Enriquez was observed based on the use of space by Filipino diners.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Fast food restaurants -- Philippines -- Space utilization; Dining room furniture -- Philippines